1996
DOI: 10.1111/j.1475-097x.1996.tb00567.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise capacity in heart failure patients: relative importance of heart and skeletal muscle

Abstract: The knee extensor and the whole-body exercise capacities were measured in 11 chronic heart failure (CHF) patients and 11 healthy age- and sex-matched controls, and were related to ejection fraction and to biochemical and histochemical markers of the musculature. The CHF patients had a 39% lower maximal oxygen uptake measured on an ergometer cycle than the healthy controls (1.54 +/- 0.57 vs. 2.51 +/- 0.70 1 min-1, P < 0.001). The low exercise capacity was markedly related to the ejection fraction (r = 0.77, P <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 31 publications
(26 reference statements)
5
42
0
Order By: Relevance
“…Many studies, including the close relation between peak V O 2 and mitochondrial enzyme activity or volume, 3,4,28 have pointed out that impaired aerobic metabolism may play a role in the limitation of systemic exercise capacity. The decreased oxidative capacity and altered mitochondrial regulation and energy transfer demonstrated here could be the mechanistic basis for decreased oxygen utilization and exercise capacity in CHF.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies, including the close relation between peak V O 2 and mitochondrial enzyme activity or volume, 3,4,28 have pointed out that impaired aerobic metabolism may play a role in the limitation of systemic exercise capacity. The decreased oxidative capacity and altered mitochondrial regulation and energy transfer demonstrated here could be the mechanistic basis for decreased oxygen utilization and exercise capacity in CHF.…”
Section: Discussionmentioning
confidence: 99%
“…HFPEF, heart failure with preserved ejection fraction; HC, healthy age-matched control. have reported that the capillary-to-fiber ratio is also reduced in HFREF patients compared with HC subjects (42,43,58,64,72).…”
Section: Discussionmentioning
confidence: 99%
“…However, our results are believable given what is known from many reports regarding skeletal muscle fiber composition and capillarity in patients with HFREF and other populations. Specifically, several investigators have reported that HFREF patients have decreased type I fibers compared with HC subjects (12,39,42,45,64,66,67) and that this is related to peak V O 2 (49). Moreover, several investigators Values are means Ϯ SD or numbers of patients/subjects per group (n) with percentages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, the literature is equivocal regarding the effects of CHF on skeletal muscle oxidative metabolism. For instance, some studies report that HFrEF induces significant structural/functional mitochondrial impairments and/or reductions in oxidative enzyme capacity (68,156,197,281,297) that vary as function of disease severity (14,61,65), whereas others do not (90,154,210,274,305,319,340). Recently, impaired skeletal muscle oxidative metabolism has also been reported in HFpEF patients (37) and animal models (43,333).…”
Section: Exercising Blood-muscle O 2 Flux In Health and Chf: Mechanismentioning
confidence: 99%